(untitled) (Economic and Political Thought, 2024)
The purpose of the article is to demonstrate the possibility of studying some economic aspects of tourism in the light of the KLEMS productivity account from the field of economic growth accounting. The theoretical part points out the special importance of residually calculated MFP for economic growth at the level of sectors and industries of the economy, in addition to the basic production factors. The results of the calculations are demonstrated and their preliminary interpretation is made, thus demonstrating the effectiveness of the KLEMS productivity accounting in economic analysis at the sectoral level using the example of section I according to NACE rev. 2.